EFFECTS OF CONTEXT CLUES AND STUDENTS’ GENDER ON IPS STUDENTS’ READING COMPREHENSION OF ANECDOTE TEXT - Akhmad Ali Mirza (Jurnal Pendidikan Surya Edukasi (JPSE), 2016)
This study was conducted to find out whether or not there was effect of gender on IPS students’ reading comprehension of anecdote text and effect of context clues on IPS students’ reading comprehension of anecdote text. This study was also conducted to find out whether or not there was interaction effect of gender and context clues on IPS students’ reading comprehension of anecdote text. The context clues used in this study were definition and synonym context clues. The subject of this study was the students of IPS Program of SMUN 1 Palangka Raya academic year 2009/2010. Test was used as instrument in order to collect the data needed. There was only one kind of test in this study, it was the reading comprehension test, and it was in the form of multiple choice question. The writer used experimental method in this study. The data were processed and analyzed according to these steps: giving the treatment, checking and scoring, analyzing the data by using statistic technique of ANOVA, and making the conclusion based on the analysis. The result of this study shows that there is no significant effect of gender on IPS students’ reading comprehension of anecdote text, there is no significant effect of context clues on IPS students’ reading comprehension of anecdote text, and there is no significant interaction effect of gender and context clues on IPS students’ reading comprehension of anecdote text.